Rescue and Conservation of Male Adult Alpacas (Vicugna pacos) Based on Spermatogonial Stem Cell Biotechnology Using Atomized Black Maca as a Supplement of Cryopreservation Medium - Valdivia, Martha; Bravo, Zezé; Reyes, Jhakelin; Gonzales, Gustavo F. (Frontiers in Veterinary Science, 2021)
It’s the first time that, after 24 hours postmortem the testes tissue (n=44) and isolated testicular cells (n=51) from adults alpaca were frozen at -196°C in freezing media and protocols of cryopreservation designed by us. Fragments of testes tissue (25mg) in medium MTDB: HAM-F10 modified medium (M) with 0,2M Trehalose (T), 10%DMSO (D), and isolated testes cells in medium MSDB: HAM-F10 modified media contained Sucrose (0.2M), DMSO (10%) were frozen. Atomized Black (B) Maca (20mg/ml) as a natural supplement added in both media. Before and after In vitro proliferation of spermatogonial isolated cells were cryopreserved. Percentage of cell viability after cryopreservation using Trypan blue were done in cells from fragments (73.75±4.58%) and isolated cells (52.49±3.30) thawed showed significant differences (p˂0.05). Spermatogonial stem cells (SSC) were evaluated by flow cytometry before and after cryopreservation identified with Dolichos biflorus agglutinin as strong positive (sDBA+): 8.43±3.37 (from fragments), 1.46±0.34% (isolated SSC before proliferation) with pvalue<0,05 and after proliferation (6.29±1,17)% and 7.66±1.13% in fresh isolated SSC (p>0,05). After thawed the intact mitochondrial membrane potential activity was evaluated, as strong Mitosense showed 57±9.57% (fragments), 70.78±3.04% (isolated cells before proliferation) and 77.14±2.91% (isolated cells after proliferation) and 81.40±2.33% in freshly isolated cells. In conclusion, the black Maca showed antioxidant properties when included in the freezing media to improve the conservation of alpaca SSC. Besides, by proliferating isolated cells In vitro, they guarantee a greater quantity of SSC after thawing for subsequent preclinical or clinical work.